IMPROVEMENT OF SHORT STORY TEXT READING ABILITY THROUGH COOPERATIVE LEARNING MODEL FOR CLASS XI STUDENTS OF SMA NEGERI 1 MANDREHE UTARA LEARNING YEAR 2022/2023 - Florus Faawosa Gulo; Trisman Harefa; Lestari Waruwu (Jurnal Scientia, 2023)
Reading short stories is one learning that trains students in reading activities for determine students' ability to read short stories. This research method is Classroom Action Research (CAR) with procedures namely (1) planning, (2) action, (3) observation, (4) reflection. The subjects of this study were students of class XI SMA Negeri 1 Mandrehe Utara in the odd semester, there are 20 people with 14 men people and the number of women is 6 people. The results of research conducted in the field are the ability of students in reading short story texts in cycle 1, with an average value of 40.75% with the lowest value 0 and the highest value 75. Meanwhile in cycle II, with an average score of 83.43% with a lowest score of 72.5 and a highest score of 90. The results of observations of researchers in the first cycle of the first meeting, 67% did not implemented 33% and the second meeting, implemented 78% not implemented 22%. While in cycle I| the first meeting, carried out 83% did not implemented 17% and the second meeting, implemented 94% not implemented 6%. The results of observations of students in the first cycle of the first meeting, active 55% inactive 45% and the second meeting, active 65% not active 35%. While in cycle II the first meeting, active 68.5% inactive 31.5% and the second meeting, active 87% inactive 13%. Based on the research results, it can be concluded that the use Cooperative Learning learning models can improve abilities students reading short story texts of class XI SMA Negeri 1 Mandrehe Utara. Suggestions that are recommended are (1) it is expected that students will improve how to learn in reading short story texts, (2) the results of this study can be add knowledge in learning Indonesian, especially at short story reading material, (3) as a reference to researchers furthermore. Keywords: Reading Short Story Texts, Cooperative Learning Model Learning